Three new species of Navicula (Bacillariophyta) from lakes in Yunnan Plateau (China) - Gong, Zhijun; Metzeltin, Ditmar; Li, Yanling; Edlund, Mark (Phytotaxa, 2015)
Three new freshwater diatoms are described from China’s Yunnan Plateau region in sediments from Lakes Fuxian, Erhai, and Lugu. Navicula craticuloides, nov. sp., N. gongii, nov. sp. and N. yunnanensis, nov. sp. were identified from light and scanning electron micrographs. The main features of N. craticuloides are its valve outline with rounded ends, a narrow-lateral raphe, hooked terminal fissures, a linear axial area, a rectangular central area, and wavy striae towards the margins. The main features of N. gongii are narrowly lanceolate valves with long-protracted ends, a lateral raphe, a slightly curved axial area, and a rhombic or transversely expanded central area. The main features of N. yunnanensis are lanceolate valves with triundulate margins and cuneate ends and a lateral raphe. The new species have so far been found mainly in surficial sediment.